Play Therapy as a Method of Trauma Healing in PTSD Children Victims of Flood Disaster in West Martapura, South Kalimantan - Endang Pertiwiwati; Irfan Maulana; Fitriani Az Zahra; Ida Yuliana (Fakultas Kedokteran Universitas Lambung Mangkurat, 2021)
Abstrat: Banjar Regency was recorded as the area most affected by flooding and the West Martapura District was the sub-district area that suffered the most damage. Children as disaster victims who are prone to PTSD, they need to get serious treatment so that the consequences are not prolonged and hamper their development. One form of intervention that can be applied to restore the psychological condition of children affected by disasters is counseling through play therapy. This study aims to analyze the effectiveness of Play Therapy as a Trauma Healing Method in Children With PTSD Flood Disaster Victims. The research design used a quasi-experimental one pre-post test group research design. The research subjects were 35 children with mild to moderate PTSD based on the PLC C version of the PTSD questionnaire, aged 4-6 years. The study was conducted for 5 weeks with various play therapy media and the intervention was carried out for 3 weeks. The results showed that there was a significant difference between the scores of the pretest and posttest scores on the PTSD questionnaire (p = 0.000) with the Wilcoxon test after trauma healing with the play method was performed. The conclusion of the study was trauma healing with the play therapy method is effectived for treating pediatric patients with PTSD victims of the post-flood South Kalimantan. Keywords: Trauma Healing, Play Therapy, PTSD, Flood, Children, PTSD Questionnaire